Sequential Chemical Bath Deposition of Cu2-xSe/CdS Film by Suppressing Ion-Exchange Reaction - Cai, Gangri; Lim, Iseul; Lee, Deok Yeon; Shrestha, Nabeen K.; Lee, Joong Kee; Nah, Yoon-Chae; Lee, Wonjoo; Han, Sung-Hwan (AMER CHEMICAL SOC, 2012)
Chemical bath deposition is an attractive technique to form single- and multilayered metal oxide/chalcogenide films on electrode surfaces. However, the occurrence of desorption and/or ion-exchange reaction during subsequent chemical bath deposition has so far limited preparation of multilayered metal oxide/chalcogenide films. In this paper, we report a method to prevent desorption and ion-exchange reaction of metal oxide/chalcogenide on electrode surfaces using a polyelectrolyte multilayer during sequential chemical bath deposition. By controlling the ion permeability of the polyelectrolyte multilayer, Cu2-xSe film was successfully deposited on the CdS film. The Cu2-xSe/CdS film is confirmed by UV-vis absorption spectroscopy, scanning electron microscopy, energy dispersive X-ray analysis, and X-ray powder diffractometer. Furthermore, the Cu2-xSe/CdS films were investigated as photoinduced charge transfer devices which showed photocurrents of 0.22 mA/cm(2) under illumination (I = 100 mW/cm(2)).
Keywords: METAL CHALCOGENIDE